DIFFERENTIAL MULTIPLICATIVE HYPERRINGS - L. Kamali Ardekani; Bijan Davvaz (Journal of Algebraic Systems, 2014)
There are several kinds of hyperrings, for example, Krasnerhyperrings, multiplicative hyperring, general hyperrings and$H_v$-rings. In a multiplicative hyperring, the multiplication isa hyperoperation, while the addition is a binary operation. In this paper, the notion of derivation on multiplicative hyperrings is introduced and some related properties are investigated. {bf Keywords:} multiplicative hyperring, derivation, differential hyperring.